2022
DOI: 10.2174/1381612827666210917145636
|View full text |Cite
|
Sign up to set email alerts
|

BDZs, Designer BDZs and Z-drugs: Pharmacology and Misuse Insights

Abstract: : Benzodiazepines (BZDs) are a widely prescribed class of sedative-hypnotics compounds for the treatment of a broad range of conditions as anxiety and obsessive-compulsive disorders, phobias, sleep related problems associated with insomnia and for the management of alcohol and GHB withdrawal. Zolpidem, zopiclone and zaleplon, commonly known as Z-drugs are non-benzodiazepine hypnotic drug with pharmacology similar to BDZs. Despite their usefulness, BDZs and Z-drugs present a potential for abuse and dependence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…It is worth noting that the five most dispensed drugs in this population all have potential for misuse, especially in populations with a previous history of addiction [ 11 , 14 , 20 , 21 , 41 45 ]. The use of BZD, z-drugs and pregabalin has great misuse potential [ 26 ] and has been shown to increase opioid-related mortality [ 6 11 , 13 , 20 ] and at least one of these drugs was present in the blood at the time of death in a vast majority of cases and they were among the drugs most frequently dispensed by this population in our material. Previous research suggests that individuals with opioid addiction are prescribed BZD in excessive amounts [ 15 , 16 ] and it is possible that excessive prescription of these drugs occurs in our material as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the five most dispensed drugs in this population all have potential for misuse, especially in populations with a previous history of addiction [ 11 , 14 , 20 , 21 , 41 45 ]. The use of BZD, z-drugs and pregabalin has great misuse potential [ 26 ] and has been shown to increase opioid-related mortality [ 6 11 , 13 , 20 ] and at least one of these drugs was present in the blood at the time of death in a vast majority of cases and they were among the drugs most frequently dispensed by this population in our material. Previous research suggests that individuals with opioid addiction are prescribed BZD in excessive amounts [ 15 , 16 ] and it is possible that excessive prescription of these drugs occurs in our material as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to opioids, other prescription drugs used in combination with opioids increase the risk of opioid-related death. In particular, the use of benzodiazepines (BZD), but also the use of z-drugs (zopiclone, zolpidem) and pregabalin, is widespread among opioid-addicted individuals, often involved in opioid deaths, and seems to be associated with increased mortality in combination with opioids both when prescribed and used illicitly [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. An American study on veterans who were prescribed opioids concluded that simultaneous BZD prescription increased the risk of overdose death in a dose-response manner.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the development of non-benzodiazepines or as known ‘ Z -drugs’ ( Bragg et al, 2019 ); that were introduced to the market in the 1990s ( Brandt and Leong, 2017 ). Z-drugs have fewer side effects owing to their short half-live, selective drug profiles, and fewer drug-drug interactions ( Zaami et al, 2021 ). Zopiclone (ZP) is a type A γ-aminobutyric acid (GABA) receptor agonist that increases GABA-neuronal block ( Louzada et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, an increase in the number of self-reported benzodiazepine use (from one subject in 2015 to 152 in 2022 and 92 in 2023), was registered. The widespread availability of benzodiazepines and their relatively low cost increases the potential for the non-medical use of these medications [50].…”
Section: Discussionmentioning
confidence: 99%